Mutual Inductance of Two Coplanar Rectangular Contours with Symmetrical Internal Arrangement - G. N. Tsitsikian; A. I. Senchenko (Известия высших учебных заведений России: Радиоэлектроника, 2018)
The expediency of developing expressions for mutual inductance of rectangular and square coplanar contours is caused by configuration of frame antennas typical for RFID-technologies. Expressions presented in this article are aimed at simplifying calculation of induction coefficients when designing loop antennas. Expressions for mutual inductance of rectangular coplanar contours with symmetrical internal arrangement are obtained on the basis of the method of sections. It is shown that under certain conditions the expressions obtained can be reduced to intrinsic inductances of the square and rectangular frames encountered in antenna configurations. The analysis allows to estimate regions of resonance frequencies of frame receiving antennas. Simultaneously, a comparative analysis of a number of expressions for the intrinsic inductance of rectangular and square frames is performed, and attention is drawn to the difference in estimates. Recommendations for clarifying square contour external inductance are provided.